RANCANG BANGUN MONITORING ENERGI LISTRIK MENGGUNAKAN SMS BERBASIS MIKROKONTROLER ATMEGA328 - Gusti Ramadhianti, Raden Ajeng; Indra Partha, Ir. Cok Gede; Raka Agung, I Gusti Agung Pt (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p19, 2018)
Customer PT. PLN (Persero) has been getting prepaid and postpaid electric service programs, on postpaid electricity PT. PLN is still using conventional ways to monitor the electricity consumption of its customers. PLN officers must record meters, calculate and publish accounts to be paid by customers. In this study using electrical energy monitoring system using SMS that can measure and monitor the use of electrical energy in real time, using the method of direct measurement. Results from the current sensor readings and voltage sensors will be forwarded to the microcontroller to be converted into the amount of electrical energy consumption and the amount of payment in accordance with tariffs that have been determined PLN. The research was conducted in Basic Laboratory of Electrical Engineering, Laboratory of Energy Conversion, Laboratory of Workshop & Electrical Installation, Electrical Engineering Study Program, Faculty of Engineering, Udayana University.